2009
DOI: 10.1063/1.3195081
|View full text |Cite
|
Sign up to set email alerts
|

Amorphization of crystalline Si due to heavy and light ion irradiation

Abstract: The formation of amorphous silicon in crystalline silicon by bombardment with light ͑Si͒ and heavy ͑Xe͒ ions has been investigated by transmission electron microscopy with in situ ion irradiation. Experiments have been carried out at room temperature and low temperature ͑50 K͒ and the results are compared to a simple numerical model for amorphization. The results indicate that the amorphization mechanisms for both irradiations are heterogeneous in nature and that numerous overlaps of the collision cascade are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 30 publications
2
22
0
1
Order By: Relevance
“…It had previously been assumed that within the confines of a collision cascade the material is always rendered amorphous thus producing spatially isolated amorphous zones [9][10][11]. Recent work on the annealing of damage created by individual collision cascades [9,12], cascade overlaps [2] and cluster/molecular ion irradiation [13,14] has indicated that this may not necessarily be true with the cascade volumes consisting of variable levels of damage ranging from dilute up to completely amorphous.…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…It had previously been assumed that within the confines of a collision cascade the material is always rendered amorphous thus producing spatially isolated amorphous zones [9][10][11]. Recent work on the annealing of damage created by individual collision cascades [9,12], cascade overlaps [2] and cluster/molecular ion irradiation [13,14] has indicated that this may not necessarily be true with the cascade volumes consisting of variable levels of damage ranging from dilute up to completely amorphous.…”
mentioning
confidence: 96%
“…Observations from Figure 1 indicate that in both irradiations, the amorphisation proceeds via a heterogeneous nucleation process rather than the homogeneous process that is generally accepted for low mass ions such as He [2]. However, a greater fluence by four-orders of magnitude (and over two-orders of magnitude greater in dpa) is required to achieve complete amorphisation in the case of He relative to Xe.…”
mentioning
confidence: 96%
See 3 more Smart Citations